Clinical, MRI and Arthroscopic Correlation in Internal Derangement of Knee - Sharma, U K; Shrestha, B K; Rijal, S; Bijukachhe, B; Barakoti, R; Banskota, B; Pradhan, I; Banskota, A K (Kathmandu University Medical Journal, 2012)
Background The traumatic or degenerative internal derangement of the knee requires certain investigations for the establishment of diagnosis, in addition to clinical history and a thorough physical examination. The use of arthrography and arthroscopy improves the accuracy of the diagnosis. MRI scanning of the knee joint has often been regarded as the noninvasive alternative to diagnostic arthroscopy. Objective The purpose of the study was to correlate clinical and low field MRI findings with arthroscopy in internal derangement of the knee. Methods Forty one patients with suspected internal derangement of the knee were subjected to MR examination followed by arthroscopy. Clinical criteria used were history, mode of injury, Mc Murray’s, Apley’s grinding, Thessaly’s test for meniscal injury. Drawer test was considered to be essential for clinical diagnosis of cruciate ligament injury. MRI of the knee was performed in low field open magnet (0.35T, Magnetom C, Seimens). Arthroscopy was done within two months of MR examination and was considered gold standard for the internal derangement of the knee. Results The sensitivity, specificity, diagnostic accuracy of clinical examination were 96.1%, 33.3% and 73.1% respectively for medial meniscal tear; 38.4%, 96.4% and 78.1% respectively for lateral meniscal tear. The sensitivity, specificity, diagnostic accuracy of MRI were 92.3%,100% and 95.1% for medial meniscal tear; 84.6%96.4% and 92.6% respectively for lateral meniscal tear. Conclusion Clinical examination showed higher sensitivity for medial meniscal tear compared to MRI, however with low specificity and diagnostic accuracy. Low field MRI showed high sensitivity, specificity, diagnostic accuracy for meniscal and cruciate ligament injury, in addition to associated derangement like articular cartilage damage, synovial thickening. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6300 Kathmandu Univ Med J 2011;9(3):174-8